The "chemical oxygen demand/total volatile acids" ratio as an anaerobic treatability indicator for landfill leachates - Contrera, Ronan Cleber; Silva, Katia Cristina da Cruz; Silva, Gustavo Henrique Ribeiro da [UNESP]; Morita, Dione Mari; Zaiat, Marcelo; Schalch, Valdir (Brazilian Soc Chemical Eng, 2015)
In some operational circumstances a fast evaluation of landfill leachate anaerobic treatability is necessary, and neither Biochemical Methane Potential nor BOD/COD ratio are fast enough. Looking for a fast indicator, this work evaluated the anaerobic treatability of landfill leachate from Sao Carlos-SP (Brazil) in a pilot scale Anaerobic Sequence Batch Biofilm Reactor (AnSBBR). The experiment was conducted at ambient temperature in the landfill area. After the acclimation, at a second stage of operation, the AnSBBR presented efficiency above 70%, in terms of COD removal, utilizing landfill leachate without water dilution, with an inlet COD of about 11,000 mg.L-1, a TVA/COD ratio of approximately 0.6 and reaction time equal to 7 days. To evaluate the landfill leachate biodegradability variation over time, temporal profiles of concentration were performed in the AnSBBR. The landfill leachate anaerobic biodegradability was verified to have a direct and strong relationship to the TVA/COD ratio. For a TVA/CODTotal ratio lower than 0.20, the biodegradability was considered low, for ratios between 0.20 and 0.40 it was considered medium, and above 0.40 it was considered high.
Keywords: Landfill leachate; Total volatile acids; Treatability; Biodegradability; Anaerobic sequencing batch biofilm reactors